A new species of the genus Mongolotettix Rehn, 1928 from Hubei, China (Acrididae, Acridoidea, Orthoptera) - Zheng, Fang-Qiang; Shi, Jian-Ping; Dang, Yan (Zootaxa, 2017)
The genus Mongolotettix Rehn, 1928 is a small genus of family Adrididae. It has nine species discovered from the Far Eastern Asian countries, including China, Japan, Korea, Mongolia, and Russia [Bolívar, 1898; Uvarov, 1914; Caudell, 1921; Chogsomzhav, 1974; Li et Lian, 1994; Wan, Ren et Zhang, 1998; Xie et Li, 2000, Kim et Kim 2005; Dong, et al, 2015; Shi et al, 2016; Storozhenko, 2016; Eades et al, 2017; Zhang et al, 2017]. In the present paper, we describe a new species of the genus from Hubei, China. Type specimens are deposited in the College of Plant Protection, Shandong Agricultural University, Taian, Shandong, China.